USING MOBILE APPS IN LEARNING FOREIGN LANGUAGE - Maxmanazarova Feruza Ismoilovna; Sodiqova Zarina Farhod qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study explores the role of mobile applications in foreign language learning and highlights their effectiveness in modern education. With the rapid development of technology and the increasing number of internet users worldwide, mobile learning has become a widely used method. Language learning applications provide flexible, accessible, and interactive opportunities for learners to study anytime and anywhere. Moreover, these applications support independent learning and contribute to the development of cognitive and communicative skills. The study also discusses certain limitations of mobile applications while emphasizing their overall importance in language education.